2015
DOI: 10.1038/jhh.2015.11
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between heart-carotid pulse transit time and carotid intima-media thickness in hypertensive patients

Abstract: The study aimed to investigate the relationship between heart-carotid pulse transit time and carotid intima-media thickness (CIMT) in hypertensive patients, and whether including the pre-ejection period (PEP) in heart-carotid pulse transit time would affect this correlation. A total of 62 hypertensive patients were included in this study. They were divided into the normal CIMT group (n=33, CIMT⩽0.8 mm) and the thickened CIMT group (n=29, CIMT>0.8 mm). The noninvasive ultrasound method was used to measure CIMT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…While BPV has been widely studied in hypertension [ 34 , 62 ], less is known about its relationship with mental illness. Several studies have reported an increase in BPV in individuals with mental illness, which has been linked to an increase in their cardiovascular risk and target organ damage.…”
Section: Introductionmentioning
confidence: 99%
“…While BPV has been widely studied in hypertension [ 34 , 62 ], less is known about its relationship with mental illness. Several studies have reported an increase in BPV in individuals with mental illness, which has been linked to an increase in their cardiovascular risk and target organ damage.…”
Section: Introductionmentioning
confidence: 99%
“…Given that we have already accurately measured individual heartbeats represented by R-R intervals in the anterior chest using IR-UWB radar in our previous study 17 , accurate measurement of individual R-R intervals from the carotid artery may open the possibility for noncontact measurement of the pulse transit time using radar. The pulse transit time contains information associated with the stiffness of the artery and has already been widely exploited to assess the degree of atherosclerosis and vascular aging 27,28 . Therefore, accurate measurement of the carotid pulse would widely expand the applications of IR-UWB radar in the clinical cardiovascular field.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the blood pressure is represented by the carotid pulse [3][4] [5]. The carotid pulse records carotid artery pressure signals; the record is done by placing a sensor on the neck and is an alternative to seeing blood pressure signals [6] [5]. This carotid pulse is also useful for phonocardiograph (PCG) and can help identify a second heart (S2) and its components.…”
Section: Introductionmentioning
confidence: 99%